Spatial analysis of fish species composition in relation to fishing gear in the upper stream of Brantas River, Malang, East Java, Indonesia - ARIEF SETYANTO; DADUK SETYOHADI; VIGA BALLACKA IRAWAN; SRI SUDARYANTI; NICO CAESAR; WAHYU ENDRA KUSUMA; AKHMAD TAUFIQ MUKTI; ANDIK ISDIANTO; WIRASTIKA ADIHAPSARI; EVELLINE DEWI LUSIANA; ANDRIA ANSRI UTAMA; ANDHIKA PRIMA PRASETYO; RANI EKAWATY; WINDRA NEKA; NORA AKBARSYAH (Society for Indonesian Biodiversity, 2025)
Abstract. Setyanto A, Setyohadi D, Irawan VB, Sudaryanti S, Caesar N, Kusuma WE, Mukti AT, Isdianto A, Adihapsari W, Lusiana ED, Utama AA, Prasetyo AP, Ekawaty R, Neka W, Akbarsyah N. 2025. Spatial analysis of fish species composition in relation to fishing gear in the upper stream of Brantas River, Malang, East Java, Indonesia. Biodiversitas 26: 4193-4200. Inland water ecosystems in Indonesia, particularly in East Java with the Brantas River, hold significant potential for capture fisheries and aquaculture. Covering an area of 13.85 million hectares, this ecosystem includes rivers, natural lakes, and man-made reservoirs. The potential fish resources are projected to be substantial, with the capacity to enhance employment opportunities and boost regional income. However, the management and utilization of fisheries resources in inland waters remain underdeveloped, requiring optimization through appropriate policies and supportive infrastructure. The upper stream of the Brantas River not only provides water for industries and local water utilities but also functions as a critical habitat for various fish species, despite being predominantly managed by small-scale fishers. This study aims to evaluate the composition of fish catches based on fishing area and gear type in the Malang Raya Region of the Brantas River. A descriptive approach was employed for data collection, using random sampling from fishers at seven designated sampling stations. Data were collected within the rainy season through direct observation, interviews, and documentation. Statistical analysis was performed using ANOVA and Chi-Square methods, utilizing Microsoft Excel and SPSS version 27. The results indicate that variations in species composition of the catch were significantly influenced by the sampling stations and the types of fishing gear used.